Phonon thermal conductivity of the stanene/hBN van der Waals heterostructure. Issue 18 (4th May 2021) - Rahman, Md. Habibur; Islam, Md Shahriar; Islam, Md Saniul; Chowdhury, Emdadul Haque; Bose, Pritom; Jayan, Rahul; Islam, Md Mahbubul
Abstract : We found that the phonon thermal conductivity (PTC) of bare hBN and stanene could be engineered by assembling them in the form of a vertical heterostructure. Abstract : We use classical non-equilibrium molecular dynamics (NEMD) simulations to investigate the phonon thermal conductivity (PTC) of hexagonal boron nitride (hBN) supported stanene. At first, we examine the length dependent PTCs of bare stanene and hBN, and the stanene/hBN heterostructure and realize the dominance of the hBN layer to dictate the PTC in the heterostructure system. Afterward, we assess the length-independent bulk PTCs of these materials. The bulk PTCs at room temperature are found as ∼15.20 W m −1 K −1, ∼550 W m −1 K −1, and ∼232 W m −1 K −1 for bare stanene and hBN, and stanene/hBN, respectively. Moreover, our simulations reveal that bare stanene exhibits a substantially lower PTC compared to bare hBN, and the predicted PTC of stanene/hBN lies between those of stand-alone stanene and hBN. We also found that the PTC obtained for the stanene/hBN system from NEMD simulations nicely agrees with the theoretical formula developed to predict the PTC of heterostructures of two distinct materials. Temperature studies suggest that the PTC of the stanene/hBN heterostructure system follows a decreasing trend with increasing temperature. Additionally, corresponding phonon density of states (PDOS) and phonon dispersion data are provided to comprehensively understand the phonon properties of bare stanene and hBN, and stanene/hBN. Overall, this NEMD study would offer a deep understating towards the PTC of the stanene/hBN heterostructure and would widen the scope of its successful operations in future nanoelectronic, spintronic, and thermoelectric devices.